2022
DOI: 10.1038/s41467-022-30556-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a nucleo-adhesome

Abstract: In addition to central functions in cell adhesion signalling, integrin-associated proteins have wider roles at sites distal to adhesion receptors. In experimentally defined adhesomes, we noticed that there is clear enrichment of proteins that localise to the nucleus, and conversely, we now report that nuclear proteomes contain a class of adhesome components that localise to the nucleus. We here define a nucleo-adhesome, providing experimental evidence for a remarkable scale of nuclear localisation of adhesion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…Conceptually, the presence of VE-cadherin in the nucleus remains challenging. Recently, a proteomic seminal approach reported by Adam Bryon et al [46] showed that some adhesion proteins like integrin and others involved in adherents junctions have nuclear localization and are called nucleo-adhesome regions nearly to the nucleus. More interestingly, the proteins associated with nucleo-adhesome are FAK-dependent way.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, the presence of VE-cadherin in the nucleus remains challenging. Recently, a proteomic seminal approach reported by Adam Bryon et al [46] showed that some adhesion proteins like integrin and others involved in adherents junctions have nuclear localization and are called nucleo-adhesome regions nearly to the nucleus. More interestingly, the proteins associated with nucleo-adhesome are FAK-dependent way.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, on the other hand, the mechanism is not properly regulated and FAK is overexpressed [ 39 41 ]. Control melanoma cells have significant focal points and vinculin around the nucleus, the latter likely resulting from interactions with talin localized in the cell nucleus [ 42 , 43 ]. In treated melanoma cells, we found vinculin to be delocalized over the entire cytoplasmic fluid, consistent with an increase in its inactive form, which is consistent with the activation of FAK regulation mechanisms [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complexes center on integrin receptors that bind a variety of ECM proteins outside the cell, and a number of adaptor proteins and secondary messengers on their short cytoplasmic tails inside the cell. These adaptors form the direct connection to the cytoskeleton ( Burridge, 2017 ; Byron et al, 2022 ). As mentioned previously, FAs are also major sites of mechanosensing, so the signals received from the ECM range from chemical to physical.…”
Section: Cell Adhesion Proteins As Gene Regulatorsmentioning
confidence: 99%
“…Interestingly, in a major study demonstrating Zyxin’s translocation to the nucleus ( Cattaruzza et al, 2004 ), Vinculin, another well-known mechanosensing adaptor and Actin binding protein, did not shuttle to the nucleus under the same conditions, suggesting some specificity of Zyxin to proteins that will participate in both Actin binding and nuclear transport. Additionally, several key signaling partners to these adaptors such as FAK ( Griffith et al, 2021 ) and ICAP-1 ( Draheim et al, 2017 ), have also been detected in the nucleus under certain conditions, possibly creating a specific nucleo-adhesome protein pool with specific functions to be explored ( Byron et al, 2022 ).…”
Section: Cell Adhesion Proteins As Gene Regulatorsmentioning
confidence: 99%